Groundwater usage and strategic complements, Part I, Instrumental variables - Caleb M. Koch; Heinrich H. Nax (Games, 2022)
We test whether the decisions in a common-pool resource game are better modeled game- theoretically as strategic substitutes or complements using an individual-level dataset of groundwater usage that accounts for 3% of US irrigated agriculture. Based on a regression framework with instrumental variables, we find support for strategic complements, suggesting that reciprocity- and/or race-to-depletion-like dynamics are key to understanding groundwater usage.
Keywords: C72; Q12; Q20; Q25; 330; common-pool resources; US agriculture; groundwater; dynamic game theory; panel data; identification